The Investigation of Clinical Guidelines and Standards on Infection Control in Specialized Dental Departments - Ali Keshvad, Mohammad; Taghi Vatandoust, Mohammad; Tahmasebi, Elahe; Yazdanian, Mohsen; Sanaeinasab, Hormoz; Salesi, Mahmood; Rafiei, Esmaeil (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: It is important to adhere to infection control measures in dental procedures due to direct contact with blood and saliva. During the Coronavirus disease 2019 pandemic, regular surveillance is imperative to ensure adherence to the standards. This study aimed to assess the level of adherence to infection control guidelines in specialized dental clinics in different working shifts. Materials and Methods: This study was assessed the level of adherence of 45 selected dental departments to three main guidelines released by (I) the Center for Disease Control (CDC), (II) Ministry of Health (MOH), and (III) armed forces organization (AFO) in three different working shift. The CDC checklist had eight domains. Thus, the items of each domain were individually scored, and considering the weighting coefficient of each item, the total score was calculated. The same procedure was carried out for the two remaining guidelines. Possible effect of working shifts and different specialties on infection control practice was also calculated. Results: The mean rate of adherence was 70.7% to the CDC, 93.8% to the MOH and 84.4% to the AFO guidelines indicating that adherence to the CDC guidelines was lower than the other two domestic guidelines. Individual assessment of each item revealed that hand hygiene (39%) and safe handling and disposal of sharp instruments (46%) acquired the lowest, and sterilization (79%) and safe injection (97%) acquired the highest score according to the CDC checklist. There was no relationship between working shifts and dental specialties regarding the adherence to infection control standards. Conclusion: Dental clinics had different performances regarding infection control guidelines. Further emphasis should be placed on hand hygiene and disposal of sharp instruments.